Molecular simulations of hevein/(GlcNAc)3 complex with weakened OH/O and CH/π hydrogen bonds: implications for their role in complex stabilization - Mareška, Václav; Tvaroška, Igor; Králová, Blanka; Spiwok, Vojtěch (Carbohydrate research, 2015)
Carbohydrate-protein complexes are often characterized by interactions via aromatic amino acid residues. Several mechanisms have been proposed to explain these stacking-like interactions between pyranose sugars and aromatic moieties. The physical basis of these interactions is being explained as either dispersion CH/π or hydrophobic. In order to elucidate the nature of these interactions, we performed a series of molecular dynamics simulation of hevein domain (HEV32) in complex with (β-D-GlcNAc)3. Selected OH/O and CH/π hydrogen bonds involved in carbohydrate recognition were artificially weakened in 100 ns molecular dynamics simulations. Separate weakening of either OH/O or CH/π hydrogen bonds was not sufficient to destabilize the complex. This indicates that other effects, not solely CH/π dispersion interactions, contribute significantly to the stability of the complex. Significant destabilization of complexes was reached only by simultaneous weakening of OH/O and CH/π hydrogen bonds. This also shows that classical hydrogen bonds and CH/π interactions are working in concert to stabilize this carbohydrate-protein test case.
Keywords: Antimicrobial Cationic Peptides; Models, Molecular; vodíková vazba; Hevein domain; CH/π interactions; rostlinné lektiny; kationické antimikrobiální peptidy; Binding Sites; Plant Lectins; vazebná místa; Carbohydrate Sequence; Molecular dynamics simulation; Carbohydrate Conformation; Hydrogen Bonding; molekulární modely; konformace sacharidů; Carbohydrate–aromatic interactions; Hydrogen; Trisaccharides; Molecular Dynamics Simulation; sacharidové sekvence; vodík; trisacharidy; simulace molekulární dynamiky; Hydrophobic effect